The distinct structural preferences of tau protein repeat domains. Issue 45 (18th May 2018) - Li, Xuhua; Dong, Xuewei; Wei, Guanghong; Margittai, Martin; Nussinov, Ruth; Ma, Buyong
Abstract : Among the four bi-repeat protofilaments, only R3–R4 can maintain the C-shaped structure that can be stabilized by heparins, while R1–R2 tends to be linear in shape, and these two structural motifs appear in the most stable K18 protofilament. Abstract : The tau fibrillar structures from the brain of an Alzheimer's patient have a core with a C-shaped motif of the third and fourth repeat domains (R3–R4). Our simulations indicated that the C-shaped motif is only stable for R3–R4, while R1–R2 tends to be linear in shape. These two structural motifs appear in the most stable K18 protofilament. Heparin can further stabilize the C-shaped R3–R4 motif, but not other repeats.